(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Mechanical impact of the contact lenses (CL) on a surface of a cornea and conjunctivas, long hypoxemic stress are the factors causing violation of stability of a plaintive film and emergence of symptoms of SSG. Research objective: assessment of efficiency of application of substitute of tears at the symptomatic SSG arising at long carrying contact lenses. Results of application of a therapy of replacement of a tear on the basis of hyaluronic acid were analysed (Oksial) at symptomatic SSG. 20 patients (40 eyes) are examined. Evaluation criteria: results of test of Norn, Shirmera, confocal microscopy of a cornea, impression cytology, extent of coloring of a conjunctiva lissaminovy green. After a course of therapy of replacement of a tear (1 month) when carrying CL the level of a total products of tears increased in comparison with initial by 11.4%, the indicator of test of Norn (VRSP) increased by 65.3%. At confocal microscopy and a cytologic research noted restoration of structure of an epithelium of a cornea and conjunctiva, extent of coloring of a conjunctiva vital dye decreased. Application of substitute of tears on the basis of hyaluronic acid is expedient for knocking over of symptoms and eduction of risk of progressing of "a dry eye" when carrying contact lenses and also for the purpose of its prevention.